Effects of printing direction on quasi‐static and dynamic compressive behavior of 3D printed short fiber reinforced polyamide‐based composites. (15th April 2022) - Wang, Kui; Xiang, Jiangyang; Wang, Jin; Xie, Guoquan; Liu, Yisen; Peng, Yong; Rao, Yanni; Matadi Boumbimba, Rodrigue
Abstract: This paper investigated the effects of printing directions (path of nozzle movement) and strain rates on the performances of short carbon and glass fibers filled polyamide‐based composites prepared by fused deposition modeling (FDM). Cylindrical specimens printed in three different printing directions were compressed at a wide range of strain rate. The results showed that, for short fiber reinforced polyamide, the compressive properties of cylindrical specimens were affected by printing directions closely associated with the fiber orientation. The highest elastic modulus and yield strength of short fiber reinforced specimens were obtained when the printing direction was parallel to the applied loading direction, because the orientation of short fibers was preferred to the printing direction. However, at large deformation, the orientation of fibers in specimens changed, accompanied by a decrease in stress. With increasing strain rates, the short fiber reinforced polyamide with different fiber orientations showed different failure modes. However, the compressive behaviors of pure polyamide were similar, although they were printed in different printing directions.